Improved thermoelectric properties in ceramic composites based on Ca3Co4O9 and Na2Ca2Nb4O13 - R. Hinterding (Elsevier, 2021)
The oxide materials Ca3Co4O9 and Na2Ca2Nb4O13 were combined in a new ceramic composite with promising synergistic thermoelectric properties. Both compounds show a plate-like crystal shape and similar aspect ratios but the matrix material Ca3Co4O9 with lateral sizes of less than 500 nm is about two orders of magnitude smaller. Uniaxial pressing of the mixed compound powders was used to produce porous ceramics after conventional sintering. Reactions between both compounds and their compositions were thoroughly investigated. In comparison to pure Ca3Co4O9, mixing with low amounts of Na2Ca2Nb4O13 proved to be beneficial for the overall thermoelectric properties. A maximum figure-of-merit of zT = 0.32 at 1073 K and therefore an improvement of about 19% was achieved by the ceramic composites.